Evaluation of Financial Performance with the Balanced Scorecard Approach in Retail Companies - Judijanto, Loso; Wenno, Meiske; Faisal, Muhammad; Arifin, Hasmia Melati; Regar, Erfendi (West Science Business and Management, 2024)
This research assesses the financial performance of retail enterprises utilizing the Balanced Scorecard (BSC) methodology. The study used a quantitative methodology, gathering data from 75 retail firms via a Likert-scale questionnaire (1 to 5). The analysis use SPSS version 26, concentrating on four key Balanced Scorecard perspectives: financial, customer, internal business processes, and learning and growth. The findings indicate substantial positive relationships across the customer, internal processes, and learning and growth perspectives with financial success, with the customer viewpoint serving as the most robust predictor. The results indicate that retail firms can improve financial performance by prioritizing customer satisfaction, operational efficiency, and ongoing innovation. These insights offer significant recommendations for retail managers seeking to synchronize strategic objectives with operational performance.